Lactate from the tumor microenvironment - A key obstacle in NK cell-based immunotherapies - Jedlička, Marek; Feglarová, Tereza; Janstová, Lucie; Hortová-Kohoutková, Marcela; Frič, Jan (Frontiers in Immunology, 2022)
Recent findings of the new roles of lactate have changed our understanding of this end product of glycolysis or fermentation. Interestingly, lactate and lactate dehydrogenase (LDHA) were reported as important markers of poor prognosis of many cancers and as the regulators of many functions of immune cells. The role of lactate as a waste molecule of metabolism has been completely reconsidered, furthermore it is now well accepted that lactate can also serve as a signaling molecule or even a fuel for cancer cells in a glucose-restricted environment. However, one of the remaining questions is the lactate immunomodulatory role in the tumour microenvironment (TME) and whether this effect can be considered a novel therapeutic target. Lactate is one of the major obstacles to immune cell effector functions and its presence in TME leads to polarization of immunosuppressive phenotypes of dendritic cells and impaired killing in the case of T cells and NK cells. This review describes the current understanding of lactate's role in tumour biology, including the broader context of the field of cancer therapy including cell-based immunotherapy, where we discuss possible lactate-caused setbacks. Finally, the possible interventions of immune cell functions targeted modulation of TME and the impact on cellular immunotherapy and therapeutic cell productions to overcome the inhibitory role of a lactate-rich environment are overviewed and discussed.